Data assimilation and the adjoint method: an overview - Taylor, Gerald D., author; Cooperative Institute for Research in the Atmosphere (Fort Collins, Colo.), publisher (Colorado State University. Libraries, 1991)
In this note a general description of the application of the adjoint method for four dimensional data assimilation is given. The main focus of this discussion is that this method when applied to a discrete model is simply an application of the chair rule of multivariate calculus to compute the gradient of a real valued function of several variables. Several different time differencing schemes are considered, as well as, two examples of discrete models.
May 1991.
Keywords: Meteorology -- Data processing; Numerical weather forecasting